2020
DOI: 10.1186/s12866-020-01893-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and taxonomic characterization of arsenic (As) transforming Bacillus sp. strain IIIJ3–1 isolated from As-contaminated groundwater of Brahmaputra river basin, India

Abstract: Background: Microbe-mediated redox transformation of arsenic (As) leading to its mobilization has become a serious environmental concern in various subsurface ecosystems especially within the alluvial aquifers. However, detailed taxonomic and eco-physiological attributes of indigenous bacteria from As impacted aquifer of Brahmaputra river basin has remained under-studied. Results: A newly isolated As-resistant and-transforming facultative anaerobic bacterium IIIJ3-1 from Ascontaminated groundwater of Jorhat, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 108 publications
(171 reference statements)
0
11
0
Order By: Relevance
“…The rationale for the optimization process was to determine conditions of contact time, amount of the Bacillus subtilis ATCC13952, the concentration of arsenic (III) solution, the pH and the temperature that would give optimum removal of arsenic [47]. Three separate laboratory Experiments (I, II and III) were conducted on laboratory simulated arsenic (III) contaminated aqueous system using the Bacillus subtilis ATCC13952 as biosorbent for the arsenic.…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for the optimization process was to determine conditions of contact time, amount of the Bacillus subtilis ATCC13952, the concentration of arsenic (III) solution, the pH and the temperature that would give optimum removal of arsenic [47]. Three separate laboratory Experiments (I, II and III) were conducted on laboratory simulated arsenic (III) contaminated aqueous system using the Bacillus subtilis ATCC13952 as biosorbent for the arsenic.…”
Section: Resultsmentioning
confidence: 99%
“…like B. megaterium [ 83 , 84 ], B. aryabhattai [ 85 ], and B. cereus strain W2 was studied by Miyatake and Hayashi [ 86 ]. Anaerobic respiration of As 5+ by B. cereus was reported by Ghosh et al [ 71 ]. Various other studies conducted over the years have reported the ability of Bacillus spp.…”
Section: Bacillus Species and Heavy Metalsmentioning
confidence: 93%
“…Among them, As 3+ and As 5+ are the most abundant forms. As 3+ is more toxic and mobile in aqueous and oxic environments than As 5+ , which is mostly adsorbed to the sediments in an anoxic state [ 70 , 71 ]. The histidine part of cellular proteins is a target site for the interaction of thiols of cysteine residues and/or imidazolium nitrogen with As 3+ , which results in the inactivation of enzymes [ 72 ].…”
Section: Bacillus Species and Heavy Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal ions were utilized as electron donors for generating energy by bacterial isolates. Example: S. aureus strain for resistance of arsenic (As 5+ /As 3+ ) [52], Klebsiella pneumonia for resistance of mercury (Hg 2+ /Hg) [53].…”
Section: Bioremediation Of Heavy Metals By Microbial Strainsmentioning
confidence: 99%